The Relationship Between Self-Concept and Consumptive Behavior of Early Adult Caffe Visitors in Payakumbuh City - Zulfatrizal, Astania Radiva; Zulmi Yusra (Causalita, 2024)
Consumptive behavior is an activity that is driven by a desire that is very strong compared to a reasonable reason. When someone obtains something because of rational needs and no longer bases their purchases on considerations of needs, then that person is said to be engaging in consumptive behavior. One of the factors causing consumer behavior in early adulthood is a low level of self-concept. This research aims to determine the relationship between self-concept and the consumer behavior of early adult cafe visitors in Payakumbuh City. The research design used in this research is quantitative research. The population in this study are early adults who already work in Payakumbuh City. The sampling technique used was the Accidental Sampling technique with a sample size of 152 people. The measuring instrument in this research uses a self-concept and consumer behavior scale with reliability values ​​of 0.930 and 0.941. The data analysis technique used in this research is Pearson Product Moment correlation analysis. The results of this research show that there is a negative relationship between self-concept and consumer behavior in early adult cafe visitors in Payakumbuh City with a value of p=0.000 (p>0.05). From the research results it can be concluded that Ha is accepted and Ho is rejected.